Analisis Kepuasan Siswa Terhadap Layanan Administrasi Di Madrasah Aliyah Negeri 2 Halmahera Utara - Dahria Adam; Marini M. Yakub (Universitas Khairun, 2023)
This study aims to determine student satisfaction with administrative services at Madrasah Aliyah Negeri 2 Halmahera Utara and to find out the performance of administrative staff at Madrasah Aliyah Negeri 2 North Halmahera. This type of research is field research (field research) with the research approach used is ex post facto classified as quantitative. The instruments used in this study were questionnaires and documentation to be analyzed using statistical techniques and correlational regression tests which were applied to a sample of 29 students from 10% of the population, totaling 293 students. The results showed that the average score of students' expectations of administrative services was 601: 29: 5 = 4.14. (601) is the total score, 29 is the number of respondents, and 5 is the number of items (instruments) or a percentage of 4.14: 5 = 0.828 x 100 = 82.8 or 83 (rounded) with a very high category, so it can be stated that students' expectations of administrative services at Madrasah Aliyah Negeri 2 North Halmahera are classified as very high/important. And the average score of administrative employee performance on administrative services is 589: 29: 5 = 4.06 (589) is the total score, 29 is the number of respondents, and 5 is the number of instrument items) or a percentage of 4.06: 5 = 0.812 x 100 = 81.2 or 81 (rounded) with a high category, so it can be stated that students' expectations of employee performance in realizing administrative services at Madrasah Aliyah Negeri 2 North Halmahera are in a very high (satisfactory) category.